2022
DOI: 10.7759/cureus.21785
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics and Outcomes of COVID-19 Between Young and Older Patients: A Multicenter, Retrospective Cohort Study

Abstract: BackgroundOutcomes of coronavirus disease 2019 have been reported to be different in the young and elderly populations. However, previous studies examining these characteristics and differences in outcomes between the two groups had a small sample size. Therefore, in this study, we evaluate the differences between young and elderly patients using a large multicenter dataset. MethodologyWe conducted a retrospective study of 1,116 consecutive COVID-19 patients admitted to two hospitals in southern California in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Symptoms of coronavirus disease 2019 (COVID- 19) in patients are reported to vary from minor symptoms (such as headache, fatigue, and fever) to severe symptoms (such as dyspnea or hypoxia) (1)(2)(3)(4). With this wide range of clinical characteristics and disease outcomes, differences between nonelderly and old patients have also been reported (1,(5)(6)(7). Various studies have shown that old age is associated with high disease severity and mortality (8).…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of coronavirus disease 2019 (COVID- 19) in patients are reported to vary from minor symptoms (such as headache, fatigue, and fever) to severe symptoms (such as dyspnea or hypoxia) (1)(2)(3)(4). With this wide range of clinical characteristics and disease outcomes, differences between nonelderly and old patients have also been reported (1,(5)(6)(7). Various studies have shown that old age is associated with high disease severity and mortality (8).…”
Section: Introductionmentioning
confidence: 99%
“…RAB+ patients were found to be associated with a greater propensity for inpatient mortality, elevated inflammatory markers such as D-dimer, and higher rates of invasive mechanical ventilation ( p = 0.008), suggesting that EBs amongst RAB+ patients may be related to the severity of illness. Furthermore, the incidence of EBs amongst patients receiving remdesivir appeared to be higher compared to rates of bradycardia in studies of patients with COVID-19 in the literature [ 25 , 26 , 31 , 32 ]. Further comparative studies are needed to tease out the exact etiology of RAB.…”
Section: Discussionmentioning
confidence: 93%
“…Although previous COVID-19 studies have found associations between bradycardia and mortality [ 25 , 26 , 31 , 32 ], the literature is conflicting. Several cases have observed RAB followed by a return to normal HR range following withdrawal of remdesivir therapy [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Compared to younger people, older people are more likely to experience severe symptoms of COVID-19 due to decreased immune system function, chronic diseases, and organ dysfunction. [10–12] However, there was no significant difference between the deceased and surviving subgroups, possibly because they were older than the patients in the non-severe group. Indeed, there is evidence that men are significantly more likely to develop COVID-19 than women.…”
Section: Discussionmentioning
confidence: 99%